Slim enough to swim? Weight pressures for competitive swimmers and coaching implications - Reel, J. J.; Gill, D. L. (The Sport Journal, 2001)
This study has the following purposes: (1) To identify most frequently reported weight-related stressors in swimming; (2) To examine the prevalence of weight concerns among female swimmers; and (3) To determine whether body concerns/stressors in swimming are related to social physique anxiety. Participants Sixty-two female swimmers from 7 college swim teams participated. Swimmers weighed 99 to 190 pounds (M =134.21). Most swimmers reported wanting to lose weight (M=7.56 pounds), with one swimmer wanting to drop 37 pounds. Measures The Weight Pressures in Swimming (WPS) inventory was patterned after Reel & Gill's (1996) CHEER instrument that measured weight pressures in cheerleading. Internal consistency for all 10 items was low, which resulted in dropping detracting items to obtain a stronger and more reliable measure (alpha=.71 )